2013
DOI: 10.3892/ijmm.2013.1475
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of exenatide against oxidative stress-induced injury

Abstract: Myocardial ischemia/reperfusion (MI/R) leads to oxidative stress, which may in turn lead to myocardial injury. In the present study, we investigated the effects of exenatide, a glucagon-like peptide-1 (GLP-1) analogue, on oxidative stress-induced injury in vitro and in vivo. In in vitro experiments, H9c2 cells were incubated with exenatide to determine the direct cytoprotective effects of exenatide following exposure to hydrogen peroxide (H2O2). Pre-treatment with exenatide (1 nM), prior to H2O2 exposure, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 28 publications
6
69
0
Order By: Relevance
“…This was supported by another observation in which the GLP-1(28 -36) amide nonapeptide rapidly enters isolated mouse hepatocytes and targets the mitochondria, where it inhibits oxidative stress (35). In addition, it is known that GSH is important for maintaining redox levels of cells and can be used to detect cell death (9). Our results indicate that GLP-1R stimulation prevented the decrease in GSH levels in cells exposed to oxidative stress, implying the role of exendin-4 in attenuating oxidative stress-induced injury.…”
Section: Discussionmentioning
confidence: 49%
“…This was supported by another observation in which the GLP-1(28 -36) amide nonapeptide rapidly enters isolated mouse hepatocytes and targets the mitochondria, where it inhibits oxidative stress (35). In addition, it is known that GSH is important for maintaining redox levels of cells and can be used to detect cell death (9). Our results indicate that GLP-1R stimulation prevented the decrease in GSH levels in cells exposed to oxidative stress, implying the role of exendin-4 in attenuating oxidative stress-induced injury.…”
Section: Discussionmentioning
confidence: 49%
“…Accumulating evidence has revealed that AKT activation plays a crucial role in the cardioprotective effect after ischemia-reperfusion injury. Activation of the anti-apoptotic signaling pathway PI3K/AKT could regulate Bcl-2, inhibit caspase cascade activation and reduce death gene expression [32]. In our study, the improvement of cell viability and attenuation of cell apoptosis ratio by geniposide pretreatment during H/R were blocked by exendin (9-39) and LY294002 to some extent.…”
Section: Discussionmentioning
confidence: 59%
“…Physiological levels of ROS/RNS in normal oxidative metabolism play a key homeostatic role in balancing disposal rates of oxidative pressure and enzyme systems in cell proliferation and survival [27][28][29]. As levels of SOD, glutathione, and catalase are less in the cardiac system, excessive production of ROS/RNS triggers oxidative stress and aggravates ischemia-induced cardiomyocyte damage [27,30], further accelerating cardiomyocyte apoptosis and loss [31,32]. Treatment with antioxidant agents or upregulation of endogenous antioxidant enzymes could prevent excessive ROS-caused injury [4,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2 R activation also is necessary for the cardioprotective effects of ischemic postconditioning (20). Stimulating GLP1R and cAMP/PKA signaling also can prevent cardiac myocyte death (18,28). PDE3 appears to be important in regulating β-AR-stimulated cAMP-signaling modules.…”
Section: Discussionmentioning
confidence: 99%